Mechanisms and benefits of granule cell latency coding in the mouse olfactory bulb - Giridhar, Sonya; Urban, Nathaniel N. (Frontiers in Neural Circuits, 2012)
Inhibitory circuits are critical for shaping odor representations in the olfactory bulb. Individual olfactory bulb granule cells can respond to brief stimulation with extremely long (up to 1000 ms), input-specific latencies that are highly reliable. However, the mechanism and function of this long timescale activity remain unknown. We sought to elucidate the mechanism responsible for long-latency activity, and to understand the impact of widely distributed interneuron latencies on olfactory coding. We used a combination of electrophysiological, optical, and pharmacological techniques to show that long-latency inhibition is driven by late onset synaptic excitation to granule cells. We also provide evidence that tufted cells, which have intrinsic properties that favor longer latency spiking than mitral cells are the major source of this excitation. Using computational modeling, we show that widely distributed interneuron latency can increase the discriminability of similar stimuli. Thus, long-latency inhibition in the olfactory bulb requires a combination of circuit- and cellular-level mechanisms that function to improve stimulus representations.